-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathnaturalArithmetic.tex
81 lines (69 loc) · 1.72 KB
/
naturalArithmetic.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
\documentclass{article}
\usepackage{amsmath, amsthm, amssymb}
\usepackage{mathtools}
\usepackage{enumitem}
\newtheorem*{mythm*}{Theorem}
\newtheorem{mythm}{Theorem}
\newtheorem{mydef}{Definition}
\begin{document}
\begin{mythm}
For all natural numbers $m$ and $n$,
\begin{align*}
m + 0 &= m \\
m + n^+ &= (m + n)^+
\end{align*}
\end{mythm}
\begin{mythm}
For all $m$ in $\omega$, $m + 1 = m^+$.
\end{mythm}
\begin{mythm}
For all natural numbers $m$ and $n$,
\begin{align*}
m \cdot 0 &= 0 \\
m \cdot n^+ &= m \cdot n + m
\end{align*}
\end{mythm}
\begin{mythm}
(Associative Law for Addition). For all $m$, $n$, and $p$ in $\omega$,
\begin{equation*}
m + (n + p) = (m + n) + p
\end{equation*}
\end{mythm}
\begin{mythm}
For all natural numbers $m \in \omega$ and $n \in \omega$, we have $m^+ + n &= (m + n)^+$.
\end{mythm}
\begin{mythm}
(Commutative Law for Addition). For all $m$, $n$ in $\omega$,
\begin{equation*}
m + n = n + m
\end{equation*}
\end{mythm}
\begin{mythm}
(Distributive Law). For all natural numbers $m$, $n$, and $p$ in $\omega$,
\begin{equation*}
m \cdot (n + p) = m \cdot n + m \cdot p
\end{equation*}
\end{mythm}
\begin{mythm}
(Associative Law for Multiplication). For all natural numbers $m$, $n$, and $p$ in $\omega$,
\begin{equation*}
m \cdot (n \cdot p) = (m \cdot n) \cdot p
\end{equation*}
\end{mythm}
\begin{mythm}
(Commutative Law for Multiplication). For all natural numbers $m$, $n$, and $p$,
\begin{equation*}
m \cdot n = n \cdot m
\end{equation*}
\end{mythm}
\begin{mydef}
Let $E \colon \omega \times \omega \to \omega$ be the unique function satisfying
\[
E(m, n) =
\begin{cases}
E(m, 0) = 1 \\
E(m, n^+) = E(m, n) \cdot m
\end{cases}
\]
\end{mydef}
\end{document}